Implementation of Policy for Supervision and Control of Sales of Alcoholic Beverages in Jayapura City, Papua Province - Septinus Saa; Abner Herry Bajari (International Journal of Scientific Multidisciplinary Research, 2024)
The circulation of alcoholic drinks in Jayapura City is increasingly widespread and can even be said to be out of control. Alcoholic drinks are openly sold in shophouses adjacent to housing or residential areas of community members. The implementation of the Regional Regulation on Alcoholic Drinks in Jayapura City has not been successful in lowering the amount of alcoholic beverages in circulation. The purpose of this study is to determine what factors impede the implementation of the policy for supervision and control of sales of alcoholic beverages in Jayapura City, Papua Province, as well as issues pertaining to its implementation throughout the city. Descriptive and qualitative research methods were employed in this study. Techniques for documentation, interviews, and observation were used to gather data. The findings of the study demonstrate that this strategy may be effective provided it is backed by thorough and unambiguous policy text as well as an environment that is favorable to its implementation, such as agency cooperation, community involvement, and enough funding. However, a number of obstacles prevent theJayapura City's application of this policy, including economic and political interests that support the sustainability of the alcohol industry, a community culture that considers alcohol to be part of social tradition, as well as limited human resources and budget for effective supervision. Apart from that, the lack of understanding and consistency of implementing officials in enforcing policies is also a big challenge